Increased selenium and decreased iron levels in relation to risk of coronary artery disease in patients with diabetes - Tian, Mengyun; Hu, Teng; Ying, Jiajun; Cui, Hanbin; Huangfu, Ning (Frontiers in Nutrition, 2023)
Background: Observational studies have reported inconsistent associations between micronutrient levels and the risk of coronary artery disease (CAD) in diabetic patients. We aim to explore the causal association between genetically predicted concentrations of micronutrients (phosphorus, magnesium, selenium, iron, zinc, and copper) and CAD in patients with diabetes. Methods: Single nucleotide polymorphisms (SNPs) connected to serum micronutrient levels were extracted from the corresponding published genome-wide association studies (GWASs). Summary-level statistics for CAD in diabetic patients were obtained from a GWAS of 15,666 patients with diabetes. The primary analysis was carried out with the inverse variance weighted approach, and sensitivity analyses using other statistical methods were further employed to assess the robustness of the results. Results: Genetically predicted selenium level was causally associated with a higher risk of CAD in diabetic patients (odds ratio [OR]: 1.25; 95% confidence interval [CI]: 1.10–1.42; P= 5.01×10−4). While, genetically predicted iron concentrations in patients with diabetes were inversely associated with the risk of CAD (OR: 0.82; 95% CI: 0.75–0.90; P =2.16×10−5). The association pattern kept robust in most sensitivity analyses. Nominally significant associations were observed for magnesium and copper with the risk of CAD in patients with diabetes. No consistent evidence was found for the causal associations between phosphorus and zinc levels, and the risk of CAD in patients with diabetes. Conclusion: We provide consistent evidence for the causal effect of increased selenium and decreased iron levels on CAD in patients with diabetes, highlighting the necessity of micronutrient monitoring and application in these patients.